#TITLE_ALTERNATIVE# - (NIM 109 00 006), Sudibianto
Abstract: Several oceanographic parameters, i.e. Tide, Sea Water Current, Wind and Waves were studied in Pulau Kambing waters Study on tide was carried out base on one filed observation in Pulau Kambing Waters, yield a conclusion that tidal type in this area is a mixed tend to diurnal, with Formzahl Number 1.02. The tidal prediction computed based on the tidal harmonics constants, resulted from tidal harmonics analysis shows that the tidal constants is quite good to build a tidal prediction at any time epoch. One month observation of sea water current in Pulau Kambing shows that tie current condition in Pulau Kambing are dominated by the tidal current. The current data also shows the contribution of seasonal current of 0.024 m/sec flowing to the East-South East. Long term wind data in Pulau kambing were obtained by triangle interpolation toward long term wind data from Juanda Airport in Surabaya, and two points from Global Wind Model from NECP, i.e. Point 105 and 114 respectively. The results were then analyzed to investigate the monthly, seasonal and yearly variation. Extreme Frequency Analysis was carried out upon the maximum wind speed coming from the eight wind direction. Based on the wind data, significant wave height and period were computed by hind casting technique using SMB method. The same as wind analysis, computation seasonal and annual Probability Table and Wave Rose analysis were also performed. Extreme Frequency analyses were performed upon the waves coming from the eight directions, from North up to North West.